2021
DOI: 10.1093/ofid/ofab551
|View full text |Cite|
|
Sign up to set email alerts
|

Xpert MTB/RIF Use Is Associated With Earlier Treatment Initiation and Culture Conversion Among Patients With Sputum Smear-Negative Multidrug-Resistant Tuberculosis

Abstract: Background While rapid molecular diagnostic tests for tuberculosis (TB) have decreased detection time of M. tuberculosis and drug resistance, whether their use improves clinical care and outcomes is uncertain. To address these knowledge gaps, we evaluated whether use of the Xpert MTB/RIF assay impacts treatment and clinical outcome metrics among patients treated for sputum smear-negative multidrug-resistant (MDR)-TB. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…In this study, we assessed the waiting time between receiving a DST and initiating treatment and the factors associated with the waiting time for a DST, treatment, pre-treatment attrition, and treatment outcomes. Considering that the clear evidence from other studies has found that efficient diagnostics tests can expedite the process of drug-resistance testing [ 23 ], the DST waiting time in our study excluded the duration between performing a DST and reporting DST results so as to avoid the impact of the detection time of DST methods, which is different from the diagnosis delay described by other published studies [ 3 , 7 ]. As a result, the median time from first seeking medical care to receiving a DST was 24 days.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we assessed the waiting time between receiving a DST and initiating treatment and the factors associated with the waiting time for a DST, treatment, pre-treatment attrition, and treatment outcomes. Considering that the clear evidence from other studies has found that efficient diagnostics tests can expedite the process of drug-resistance testing [ 23 ], the DST waiting time in our study excluded the duration between performing a DST and reporting DST results so as to avoid the impact of the detection time of DST methods, which is different from the diagnosis delay described by other published studies [ 3 , 7 ]. As a result, the median time from first seeking medical care to receiving a DST was 24 days.…”
Section: Discussionmentioning
confidence: 99%